Tin oxide-based composite negative electrode material and preparation method and use thereof

By covering the porous carbon and carbon nanotube layers on the surface of tin oxide, the problem of volume expansion of tin dioxide in lithium-ion batteries is solved, the stability and electrochemical performance of the battery are improved, and the service life of the battery is extended.

CN115986083BActive Publication Date: 2025-01-17GUANGDONG DONGDAO NEW ENERGY +1

Patent Information

Application Number
CN202310009786.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-01-17
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

Tin dioxide will experience severe volume expansion during charging and discharging of lithium-ion batteries, resulting in electrode powdering, crushing and SEI film instability, limiting its application in lithium-ion batteries.

Method used

By synthesizing porous carbon cladding and carbon nanotube cladding containing metals in situ on the tin oxide surface, the volume change of tin oxide is restrained and buffered, the volume expansion multiple after cyclic charging and discharge is reduced, and the conductivity is improved.

Benefits of technology

It effectively prevents the powdering of composite negative electrode materials, improves electrochemical performance and fast charging performance, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004037550630000091
    Figure BDA0004037550630000091
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery negative electrode materials, and specifically relates to a tin oxide-based composite negative electrode material and its preparation method and use. The in-situ synthesis method of the present invention can enhance the bonding force between SnO2 particles, porous carbon skeletons, and carbon nanotubes, making them a firmly bonded whole. The composite negative electrode material can withstand the stress generated by the volume change of tin oxide, constrain and buffer the volume change of tin oxide, reduce the volume expansion multiple of tin oxide after cyclic charge and discharge, and further prevent the pulverization of the composite negative electrode material; at the same time, it can also improve the conductivity of the composite negative electrode material and improve the electrochemical performance of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and specifically relates to a tin oxide-based composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium / sodium ion batteries have the advantages of high open circuit voltage, high energy density, long service life, no memory effect, less pollution and low self-discharge rate. They are superior to other traditional secondary batteries in overall performance and are generally considered to be the most ideal power source for various portable electronic devices and electric vehicles. Although graphite, the negative electrode material of traditional lithium ion batteries, has good cycle stability and high cost performance, it has a low charge and discharge capacity and no advantage in volume capacity, making it difficult to meet the requirements of power systems, especially electric vehicles and hybrid electric vehicles, for high battery capacity. Therefore, it is extremely urgent to develop new lithium ion battery negative electrode materials with high specific capacity, high charge and discharge efficiency and long cycle life.

[0003] In the research of non-carbon negative electrode materials, metal oxides have attracted more and more attention due to their high theoretical lithium insertion capacity. If these high-capacity negative electrode materials can reach the level of practical application, the application scope of lithium-ion batteries will be greatly broadened. Tin dioxide has a high specific capacity (1494mAh / g) and has become a hot spot in the research of negative electrode materials for lithium / sodium-ion batteries. However, tin dioxide will experience severe volume expansion during the charge and discharge process, which can easily lead to powdering, crushing and cracking of the electrode, resulting in power failure of the current collector; and the volume change will cause the SEI film on the electrode surface to be unstable, forming cracks, which will continue to grow through the cracks. Eventually, the SEI film grows to a certain thickness and lithium ions can no longer diffuse into the electrolyte. Therefore, improving the volume expansion of tin dioxide during the charge and discharge process can promote its development and application in the field of lithium-ion batteries. Summary of the invention

[0004] In order to improve the problems existing in the prior art, the present invention provides a tin oxide-based composite negative electrode material and a preparation method and use thereof, wherein a porous carbon coating layer containing metal and a carbon nanotube coating layer are sequentially coated on the surface of tin oxide by an in-situ synthesis method. The composite negative electrode material can withstand the stress generated by the volume change of tin oxide, constrain and buffer the volume change of tin oxide, reduce the volume expansion multiple of tin oxide after cyclic charge and discharge, and further prevent the pulverization of the composite negative electrode material; at the same time, the conductive performance of the composite negative electrode material can be improved, and the electrochemical performance of the composite negative electrode material can be improved.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a tin oxide-based composite negative electrode material, the method comprising the following steps:

[0007] (1) mixing SnO2, an organic solvent 1 and a surfactant to obtain a precursor 1;

[0008] (2) mixing the precursor 1 of step (1), the transition metal salt, the organic ligand and the organic solvent 2, and performing a self-assembly reaction to obtain a precursor 2;

[0009] (3) The precursor 2 of step (2) is placed in a chemical vapor deposition furnace, heated to 600-680° C. under the protection of an inert gas and kept warm for 1-5 hours, and then an organic carbon source is introduced to react to prepare the tin oxide-based composite negative electrode material.

[0010] According to an embodiment of the present invention, in step (1), the average particle size D of SnO2 is 50 It is 10 nm to 60 nm, preferably 20 nm to 40 nm, for example, 20 nm, 25 nm, 30 nm or 40 nm.

[0011] According to an embodiment of the present invention, in step (1), the mixing temperature is room temperature.

[0012] According to an embodiment of the present invention, step (1) specifically includes the following steps: mixing SnO2 with an organic solvent 1, performing ultrasonic treatment, then adding a surfactant for stirring, and centrifuging to obtain a precursor 1. The ultrasonic treatment can make SnO2 uniformly dispersed in the organic solvent 1. The stirring can accelerate the coating effect of the surfactant to obtain the precursor 1.

[0013] According to an embodiment of the present invention, in step (1), the precursor 1 is SnO2@surfactant, that is, SnO2 coated with surfactant.

[0014] According to an embodiment of the present invention, in step (1), the surfactant is selected from at least one of N-polyvinyl pyrrolidone (PVP), cetyl trimethylammonium bromide (CTAB), polyethylene glycol (PVA) and sodium dodecyl sulfonate (SDS). The addition of the surfactant can effectively avoid the agglomeration of SnO2 and also contribute to the formation of the metal organic framework material in step (2).

[0015] According to an embodiment of the present invention, in step (1), the organic solvent 1 is selected from at least one of methanol, ethanol, propanol and acetone.

[0016] According to an embodiment of the present invention, in step (1), the volume mass ratio of the organic solvent 1 and SnO2 is 1L:(2-6)g, for example, 1L:2g, 1L:3g, 1L:4g, 1L:5g or 1L:6g.

[0017] According to an embodiment of the present invention, in step (1), the mass ratio of SnO2 to surfactant is 1:(10-30), for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30.

[0018] According to an embodiment of the present invention, in step (2), the transition metal salt is selected from at least one of chromium salts, iron salts, cobalt salts, nickel salts and copper salts. Preferably, the transition metal is selected from at least one of chromium nitrate, iron nitrate, cobalt nitrate, nickel nitrate and copper nitrate.

[0019] According to an embodiment of the present invention, in step (2), the organic ligand is selected from at least one of naphthalene tetracarboxylic anhydride, dimethylimidazole, 2,5-dihydroxyterephthalic acid, trimesic acid or terephthalic acid.

[0020] According to an embodiment of the present invention, in step (2), the organic solvent 2 is selected from at least one of methanol, ethanol, formaldehyde, acetaldehyde, DMF or water.

[0021] According to an embodiment of the present invention, in step (2), the mass ratio of the transition metal salt to the organic ligand is 1:(2-4), for example, 1:2, 1:3 or 1:4.

[0022] According to an embodiment of the present invention, in step (2), the volume ratio of the sum of the masses of the transition metal salt and the organic ligand to the organic solvent 2 is (0.01 to 0.1) g:1 mL, for example, 0.01 g:1 mL, 0.02 g:1 mL, 0.03 g:1 mL, 0.04 g:1 mL, 0.05 g:1 mL, 0.06 g:1 mL, 0.08 g:1 mL, 0.09 g:1 mL or 0.1 g:1 mL.

[0023] According to an embodiment of the present invention, in step (2), the mass ratio of the transition metal salt to the precursor 1 is 1:(15-20), for example, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.

[0024] According to an embodiment of the present invention, in step (2), the temperature of the self-assembly reaction is room temperature; and the time of the self-assembly reaction is 6 hours to 24 hours.

[0025] According to an embodiment of the present invention, in step (2), the self-assembly reaction is carried out under stirring conditions.

[0026] According to an embodiment of the present invention, in step (2), after the self-assembly reaction is completed, post-treatment steps such as centrifugal washing and vacuum drying are also included. Preferably, the vacuum drying temperature is 60-100°C.

[0027] According to an embodiment of the present invention, in step (2), the precursor 2 is SnO2@surfactant@metal-MOF, that is, SnO2 coated with surfactant coated with metal-MOF.

[0028] According to an embodiment of the present invention, in step (2), the transition metal salt and the organic ligand can generate a metal organic framework material (metal-MOF) through a self-assembly reaction, and be coated on the surface of the precursor 1 (surfactant-coated SnO2) to form a precursor 2. At the same time, the presence of the surfactant in the precursor 1 is also beneficial to the generation of the metal organic framework material.

[0029] According to an embodiment of the present invention, in step (2), the precursor 2 has a core-shell structure with the precursor 1 (surfactant-coated SnO2) as the core and the metal organic framework material as the shell, and the thickness of the shell layer (metal organic framework material) is 5nm to 10nm.

[0030] According to an embodiment of the present invention, in step (3), the temperature is raised to 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C or 680°C under the protection of an inert gas and kept for 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0031] According to an embodiment of the present invention, in step (3), the organic carbon source is selected from one or more of acetylene, ethylene, methane, ethane, propane and n-butane.

[0032] According to an embodiment of the present invention, in step (3), the inert gas is nitrogen and / or argon.

[0033] According to an embodiment of the present invention, in step (3), the heating rate is 2 to 10°C / min, such as 2 to 5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0034] According to an embodiment of the present invention, in step (3), the reaction is carried out in the presence of an organic carbon source and an inert gas.

[0035] According to an embodiment of the present invention, in step (3), the volume ratio of the organic carbon source to the inert gas is 1:(10-15), for example, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0036] According to an embodiment of the present invention, in step (3), 3 to 5 mL / min of an organic carbon source is introduced into the precursor 2 per gram.

[0037] According to an embodiment of the present invention, in step (3), the reaction temperature is 600°C to 680°C (such as 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C or 680°C), and the reaction time is 1 to 10 hours.

[0038] According to an embodiment of the present invention, in step (3), after the reaction is completed, the organic carbon source is turned off and cooled to room temperature under the protection of an inert gas to prepare a tin oxide-based composite negative electrode material.

[0039] According to an embodiment of the present invention, step (3) specifically includes the following steps: placing the precursor 2 of step (2) into a chemical vapor deposition furnace, heating it to 600°C to 680°C under the protection of an inert gas, keeping it warm for 1 to 5 hours, introducing an organic carbon source, and reacting at a temperature of 600°C to 680°C for 1 to 10 hours to prepare the tin oxide-based composite negative electrode material.

[0040] According to an embodiment of the present invention, in step (3), the tin oxide-based composite negative electrode material has a core-shell structure with SnO2 as the core and a porous carbon coating layer containing a metal and a carbon nanotube coating layer as the shell layer, wherein the thickness of the porous carbon coating layer containing the metal is 3nm to 6nm, and the thickness of the carbon nanotube coating layer is 3nm to 5nm.

[0041] According to an embodiment of the present invention, in step (3), the metal-containing porous carbon coating layer and carbon nanotube coating layer are prepared by heat treatment of surfactant and metal organic framework material, and reaction with organic carbon source. Specifically, the surfactant coated on the surface of SnO2 generates residual carbon with a porous structure during high-temperature pyrolysis, and the metal organic framework material generates transition metal atoms (Sn, Fe, Co, Ni or Cu) and a porous carbon skeleton (carbonized organic framework material (MOF)) during high-temperature pyrolysis, and the transition metal atoms are evenly distributed on the porous carbon skeleton, that is, the surfactant and the metal organic framework material form a metal-containing porous carbon coating layer after heat treatment; the transition metal atoms can also be used as a catalyst to generate carbon nanotubes on the porous carbon skeleton under the action of the organic carbon source, that is, to form a carbon nanotube layer.

[0042] The present invention also provides a tin oxide-based composite negative electrode material, which is prepared by the above method.

[0043] The present invention also provides a tin oxide-based composite negative electrode material, which includes SnO2, a porous carbon coating layer containing a metal, and a carbon nanotube coating layer; the porous carbon coating layer containing a metal is coated on the surface of SnO2, and the carbon nanotube coating layer is coated on the surface of the porous carbon coating layer containing a metal.

[0044] According to an embodiment of the present invention, the tin oxide-based composite negative electrode material has a core-shell structure, including a shell layer and a core, the core is SnO2, and the shell layer is a porous carbon coating layer containing a metal and a carbon nanotube coating layer.

[0045] According to an embodiment of the present invention, the metal-containing porous carbon coating layer is coated on the surface of SnO2, and the coating may be complete coating or partial coating.

[0046] According to an embodiment of the present invention, the carbon nanotube coating layer is coated on the surface of the porous carbon coating layer containing metal, and the coating may be complete coating or partial coating.

[0047] According to an embodiment of the present invention, the thickness of the metal-containing porous carbon coating layer is 3 nm to 6 nm, and the thickness of the carbon nanotube coating layer is 3 nm to 5 nm.

[0048] The present invention also provides the use of the tin oxide-based composite negative electrode material, which is used in a negative electrode sheet.

[0049] According to an embodiment of the present invention, the negative electrode sheet used in an electrochemical device is preferably a negative electrode sheet used in a lithium-ion battery or a negative electrode sheet used in a sodium-ion battery.

[0050] Beneficial effects of the present invention:

[0051] (1) The present invention first coats the surface of SnO2 particles with a surfactant to form a precursor 1. The coating of the surfactant is beneficial to the dispersion of SnO2 particles and the formation and coating of metal organic framework materials. Then, the metal organic framework material (metal-MOF) is coated on the surface of the precursor 1. During the high temperature pyrolysis process, the surfactant and the metal organic framework material form a porous carbon coating layer containing metal. The transition metal atoms can also serve as a catalyst to generate carbon nanotubes on the porous carbon skeleton under the action of an organic carbon source, that is, to form a carbon nanotube layer. The in-situ synthesis method of the present invention can enhance the binding force between SnO2 particles, porous carbon skeletons, and carbon nanotubes, making them a firmly bonded whole. The composite negative electrode material can withstand the stress generated by the volume change of tin oxide, constrain and buffer the volume change of tin oxide, reduce the volume expansion multiple of tin oxide after cyclic charge and discharge, and further prevent the pulverization of the composite negative electrode material. At the same time, it can also improve the conductivity of the composite negative electrode material and improve the electrochemical performance of the negative electrode material.

[0052] (2) The porous structure of porous carbon and the conductive properties of carbon nanotubes can also shorten the path of lithium ions embedded in SnO2, significantly increase the ion exchange rate of the composite negative electrode material, and improve the fast charging performance of the battery. DETAILED DESCRIPTION

[0053] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0054] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0055] Example 1

[0056] (1) 2gSnO2(D 50 20 nm) was dispersed in 1 L of methanol and ultrasonicated for 30 minutes, followed by adding 20.0 g of polyvinyl pyrrolidone (PVP), stirring for 8 h, and centrifuging to obtain precursor 1.

[0057] (2) 15 g of precursor 1, 1 g of Co(NO3)2·6H2O, 3 g of dimethylimidazole and 200 mL of methanol were mixed, stirred at room temperature for 12 hours for self-assembly reaction, centrifuged and washed, and dried at 100°C in vacuum to obtain precursor 2;

[0058] (3) Place 10 g of the precursor 2 of step (2) into a chemical vapor deposition furnace, introduce nitrogen at a flow rate of 450 mL / min, heat at a rate of 5°C / min until the temperature reaches 600°C, keep warm for 1.5 hours, then introduce acetylene at a flow rate of 30 mL / min, and continue chemical vapor deposition for 4 hours. After the reaction is completed, turn off the acetylene flow, and then cool to room temperature to obtain a tin oxide-based composite negative electrode material, wherein the tin oxide-based composite negative electrode material includes SnO2 as a core, and a porous carbon coating layer containing metal Co coated on the surface of the SnO2, and a carbon nanotube coating layer coated on the surface of the porous carbon coating layer containing metal Co; wherein the thickness of the porous carbon coating layer containing metal Co is 3 nm, and the thickness of the carbon nanotube coating layer is 5 nm.

[0059] Example 2

[0060] (1) 3gSnO2(D 50 25 nm) was dispersed in 1 L of ethanol and ultrasonicated for 120 minutes, followed by adding 40.0 g of polyvinyl pyrrolidone (PVP), stirring for 12 h, and centrifuging to obtain precursor 1.

[0061] (2) 16 g of precursor 1, 1 g of Ni(NO3)2·6H2O, 3 g of dimethylimidazole and 400 mL of ethanol were mixed, stirred at room temperature for self-assembly reaction for 12 hours, centrifuged and washed, and vacuum dried at 100°C to obtain precursor 2;

[0062] (3) Place 10 g of the precursor 2 of step (2) into a chemical vapor deposition furnace, introduce nitrogen at a flow rate of 450 mL / min, heat at a rate of 5°C / min until the temperature reaches 650°C, keep warm for 1.5 hours, then introduce ethane at a flow rate of 30 mL / min, and continue chemical vapor deposition for 1 hour. After the reaction is completed, turn off the acetylene flow, and then cool to room temperature to obtain a tin oxide-based composite negative electrode material, wherein the tin oxide-based composite negative electrode material includes SnO2 as a core, and a porous carbon coating layer containing metal Ni coated on the surface of the SnO2, and a carbon nanotube coating layer coated on the surface of the porous carbon coating layer containing metal Ni; wherein the thickness of the porous carbon coating layer containing metal Ni is 4 nm, and the thickness of the carbon nanotube coating layer is 3 nm.

[0063] Example 3

[0064] (1) (1) 20gSnO2(D 50 30 nm) was dispersed in 5 L acetone and ultrasonicated for 200 minutes, followed by adding 220.0 g polyvinyl pyrrolidone (PVP), stirring for 20 h, and centrifuging to obtain precursor 1.

[0065] (2) 15 g of precursor 1, 1 g of Cu(NO3)2, 3 g of dimethylimidazole and 200 mL of methanol were mixed, stirred at room temperature for 12 hours for self-assembly reaction, centrifuged and washed, and dried at 100°C in vacuum to obtain precursor 2;

[0066] (3) placing 10 g of the precursor 2 of step (2) into a chemical vapor deposition furnace, introducing nitrogen at a flow rate of 750 mL / min, heating at a rate of 5°C / min until the temperature reaches 640°C, keeping the temperature for 1.5 hours, and then introducing propane at a flow rate of 50 mL / min for 2 hours to carry out chemical vapor deposition. After the reaction is completed, the acetylene flow is turned off, and then cooled to room temperature to obtain a tin oxide-based composite negative electrode material, wherein the tin oxide-based composite negative electrode material includes SnO2 as a core, and a porous carbon coating layer containing metal Cu coated on the surface of the SnO2, and a carbon nanotube coating layer coated on the surface of the porous carbon coating layer containing metal Cu; wherein the thickness of the porous carbon coating layer containing metal Cu is 5 nm, and the thickness of the carbon nanotube coating layer is 4 nm.

[0067] Performance Test:

[0068] Electrochemical performance test:

[0069] Semi-electric test method: The composite negative electrode material prepared in Examples 1 to 3: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) was mixed evenly and applied on copper foil. The coated electrode was placed in a 120°C vacuum drying oven for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas. The electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio was 1:1:1). The metal lithium sheet was the counter electrode. The simulated battery test was carried out in a 5V, 10mA Xinwei battery test cabinet. The charge and discharge voltage was 0.01-1.5V, and the charge and discharge rate was 0.1C. The first week discharge capacity and first week coulomb efficiency obtained by the test are listed in Table 1.

[0070] Full battery test method: The composite negative electrode material prepared in Examples 1 to 3 was used as the negative electrode, lithium cobalt oxide was used as the positive electrode, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution was used as the electrolyte to assemble a full battery. The battery was charged and discharged at room temperature at a rate of 0.1C and 0.5C, with a voltage range of 3.0 to 4.2V. The cycle performance obtained from the test is listed in Table 1.

[0071] Table 1. Electrochemical performance test results

[0072]

[0073] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a tin oxide-based composite negative electrode material, the method comprising the following steps: (1) Mixing SnO2, an organic solvent 1 and a surfactant to obtain a precursor 1; (2) mixing the precursor 1 of step (1), the transition metal salt, the organic ligand and the organic solvent 2, and performing a self-assembly reaction to obtain the precursor 2; (3) placing the precursor 2 of step (2) into a chemical vapor deposition furnace, heating it to 600-680° C. under the protection of an inert gas and keeping it warm for 1-5 hours, then introducing an organic carbon source to react, thereby preparing the tin oxide-based composite negative electrode material; In step (1), the organic solvent 1 is selected from at least one of methanol, ethanol, propanol and acetone; the mixing temperature is room temperature; In step (2), the temperature of the self-assembly reaction is room temperature; The tin oxide-based composite negative electrode material comprises SnO2, a porous carbon coating layer containing metal and a carbon nanotube coating layer; the porous carbon coating layer containing metal is coated on the surface of SnO2, and the carbon nanotube coating layer is coated on the surface of the porous carbon coating layer containing metal.

2. The preparation method according to claim 1, wherein In step (1), the average particle size D of SnO2 is 50 The surfactant is selected from at least one of polyvinyl pyrrolidone PVP, cetyl trimethylammonium bromide CTAB, polyethylene glycol and sodium dodecyl sulfate.

3. The preparation method according to claim 1, wherein In step (1), the volume mass ratio of the organic solvent 1 to SnO2 is 1L:(2-6) g; the mass ratio of SnO2 to the surfactant is 1:(10-30).

4. The preparation method according to any one of claims 1 to 3, wherein: In step (2), the transition metal salt is selected from at least one of chromium salts, iron salts, cobalt salts, nickel salts and copper salts; the organic ligand is selected from at least one of naphthalene tetracarboxylic anhydride, dimethylimidazole, 2,5-dihydroxyterephthalic acid, trimesic acid or terephthalic acid; and the organic solvent 2 is selected from at least one of methanol, ethanol, formaldehyde, acetaldehyde, DMF or water.

5. The preparation method according to any one of claims 1 to 3, wherein: In step (2), the mass ratio of the transition metal salt to the organic ligand is 1:(2-4); the volume ratio of the sum of the mass of the transition metal salt and the organic ligand to the organic solvent 2 is (0.01-0.1) g:1 mL; and the mass ratio of the transition metal salt to the precursor 1 is 1:(15-20).

6. The preparation method according to any one of claims 1 to 3, wherein: In step (3), the organic carbon source is selected from one or more of acetylene, ethylene, methane, ethane, propane and n-butane; the heating rate is 2-10°C / min; the volume ratio of the organic carbon source to the inert gas is 1:(10-15); 3-5 mL / min of the organic carbon source is introduced into each gram of the precursor 2; the reaction temperature is 600°C-680°C, and the reaction time is 1-10 hours.

7. A tin oxide-based composite negative electrode material, prepared by the method according to any one of claims 1 to 6.

8. The tin oxide-based composite negative electrode material according to claim 7, wherein: The tin oxide-based composite negative electrode material comprises SnO2, a porous carbon coating layer containing metal and a carbon nanotube coating layer; the porous carbon coating layer containing metal is coated on the surface of SnO2, and the carbon nanotube coating layer is coated on the surface of the porous carbon coating layer containing metal.

9. The tin oxide-based composite negative electrode material according to claim 7 or 8, wherein: The tin oxide-based composite negative electrode material has a core-shell structure, including a shell layer and a core, wherein the core is SnO2, and the shell layer is a porous carbon coating layer containing metal and a carbon nanotube coating layer.

10. The tin oxide-based composite negative electrode material according to claim 8, wherein: The thickness of the metal-containing porous carbon coating layer is 3nm-6nm, and the thickness of the carbon nanotube coating layer is 3nm-5nm.

11. Use of the tin oxide-based composite negative electrode material according to any one of claims 7 to 10, which is used in a negative electrode sheet.

12. The use according to claim 11, wherein Anode sheets used in electrochemical devices.

13. The use according to claim 12, wherein Anode sheets for lithium-ion batteries or cathode sheets for sodium-ion batteries.

Citation Information

Patent Citations

  • Composite negative electrode material and preparation method thereof

    CN110854373A

  • Silicon monoxide-based composite negative electrode material and preparation method and application thereof

    CN115411241A

Cited By

  • SnO2 nanorod, preparation method and application

    CN117800387A

  • A SnO2 nanorod, its preparation method and application

    CN117800387B